2011
DOI: 10.2139/ssrn.1804511
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Allocation of Hedge Funds

Abstract: Research in hedge fund investing proposes different solutions to build optimal hedge fund portfolios. However, these solutions are direct extensions of the usual meanvariance framework, and still suffer from model risks. More complex approaches start to be used but are related to numerous estimation risk s. We compare in this paper the out-sample properties of different allocation models through a dynamic investment exercise using hedge fund indices. We show that the best out-of-sample properties are obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Elevated levels of idiosyncratic risk were considered to generate the outsize returns expected of hedge fund managers. [16] found that the desire for risk-taking led hedge fund managers to acquire skills, including actively gathering a large amount of information, developing analytical skills, and demonstrating sound judgement. The ability to follow company practice in the selection of diversified portfolios that conform to market models, represents superior performance in mutual funds.…”
Section: Risk Aversion Among Hedge Fund Traders and Mutual Fund Tradersmentioning
confidence: 99%
“…Elevated levels of idiosyncratic risk were considered to generate the outsize returns expected of hedge fund managers. [16] found that the desire for risk-taking led hedge fund managers to acquire skills, including actively gathering a large amount of information, developing analytical skills, and demonstrating sound judgement. The ability to follow company practice in the selection of diversified portfolios that conform to market models, represents superior performance in mutual funds.…”
Section: Risk Aversion Among Hedge Fund Traders and Mutual Fund Tradersmentioning
confidence: 99%
“…Currently, people are more interested in investing in hedge funds, since hedge funds' returns are very different from those of standard asset classes, which makes them attractive to investors looking for a diversified and balanced portfolio [1][2]. Therefore, the research on hedge fund investment naturally focuses on finding the optimal proportion of hedge fund investment, measuring the performance of hedge fund, identifying the risk factors of hedge fund, and finally constructing the optimal hedge fund investment portfolio [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Elliott and Miao (2009) and Guidolin and Timmermann (2004) combined the RSM with the value at risk (VaR) and conditional VaR (CVaR) and obtained significantly better performance. Bruder et al (2011), Saunders et al (2010) and Guidolin and Ria (2010) combined the Black-Litterman (BL) estimates with the RSM. Most studies focus on subcategories of only one asset class, like hedge funds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focus on subcategories of only one asset class, like hedge funds, e.g. Saunders et al (2010) and Bruder et al (2011), or stocks, e.g. Zhao (2010) and Guidolin and Timmermann (n.d.).…”
Section: Introductionmentioning
confidence: 99%